EKSPLORASI TRILOGI KEPEMIMPINAN TAMANSISWA MELALUI PERAN KEPALA SEKOLAH DI SD NEGERI GEDONGKIWO - Any Foreska; Endang Hangestiningsih (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
This study aimed to describe the exploration of the trilogy in Tamansiswa leadership by the principal’s role at Gedongkiwo Public Elementary School in the 2018/2019 school year. It used the descriptive qualitative method. The researcher investigated the subject by the principal, the first up to fifth-grade teachers, the psychical education teacher, the head of school administration officer, and the fourth and fifth-grade elementary school students. The techniques used to collect the data were observation, interview, and documentation. Moreover, the data analysis technique explained by some steps as data collection, reduction, display, and conclusion drawing. The results of this exploration study showed in the form of descriptions and tables.